2016
DOI: 10.5888/pcd13.160160
|View full text |Cite
|
Sign up to set email alerts
|

Using Photovoice and Asset Mapping to Inform a Community-Based Diabetes Intervention, Boston, Massachusetts, 2015

Abstract: IntroductionDiabetes self-management takes place within a complex social and environmental context.  This study’s objective was to examine the perceived and actual presence of community assets that may aid in diabetes control.MethodsWe conducted one 6-hour photovoice session with 11 adults with poorly controlled diabetes in Boston, Massachusetts.  Participants were recruited from census tracts with high numbers of people with poorly controlled diabetes (diabetes “hot spots”).  We coded the discussions and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 28 publications
(31 reference statements)
0
21
0
Order By: Relevance
“…As regards methodology, 10 of the 14 studies (71%) adopted Kurt Lewin’s participatory action research approach, most of which (79%) used the CBPR research model [ 27 , 30 , 31 , 35 , 37 ], while Aviñó [ 10 ], Greetham et al [ 36 ] and Matthiesen et al [ 34 ] employed the ABCD method proposed by Kretzmann and McKnight [ 3 ], and others used specific variants such as the CHAMP method for associations, which was employed by the Railton Foundation and the University of Stellenbosch in Lazarus et al [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards methodology, 10 of the 14 studies (71%) adopted Kurt Lewin’s participatory action research approach, most of which (79%) used the CBPR research model [ 27 , 30 , 31 , 35 , 37 ], while Aviñó [ 10 ], Greetham et al [ 36 ] and Matthiesen et al [ 34 ] employed the ABCD method proposed by Kretzmann and McKnight [ 3 ], and others used specific variants such as the CHAMP method for associations, which was employed by the Railton Foundation and the University of Stellenbosch in Lazarus et al [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this type of research, where the study participants are the subject of analysis (e.g., their behaviours, their discourses), even if they sometimes take an active part in the research, it is important for the researcher to take ethical considerations into account. However, these were only explicitly mentioned in six of the 14 studies reviewed (43%) [ 29 , 30 , 31 , 34 , 35 , 37 ]. However, since the report by Greetham et al [ 36 ] was a pilot study funded by the National Health Service, it can be assumed that it observed ethical principles.…”
Section: Resultsmentioning
confidence: 99%
“…Photovoice is a participatory research method where participants use photography and accompanying narrative to describe their lived experiences in relation to a certain topic, in this case, diabetes self-management. Our study showed that photovoice had the potential to help participants gain insight to their illness, motivate behavioral change (Florian et al, 2016), and could be a useful intervention to improve diabetes control.…”
Section: Introductionmentioning
confidence: 85%
“…To improve understanding of factors that prevent patients in these hotspots from achieving better diabetes control, and to inform future interventions, we previously conducted a study incorporating photovoice methodology (Florian et al, 2016). Photovoice is a participatory research method where participants use photography and accompanying narrative to describe their lived experiences in relation to a certain topic, in this case, diabetes self-management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation